The interaction of child abuse and rs1360780 of the FKBP5 gene is associated with amygdala resting‐state functional connectivity in young adults. Issue 10 (5th April 2021) - Wesarg, Christiane; Veer, Ilya M.; Oei, Nicole Y. L.; Daedelow, Laura S.; Lett, Tristram A.; Banaschewski, Tobias; Barker, Gareth J.; Bokde, Arun L.W.; Quinlan, Erin Burke; Desrivières, Sylvane; Flor, Herta; Grigis, Antoine; et al.
Abstract: Extensive research has demonstrated that rs1360780, a common single nucleotide polymorphism within the FKBP5 gene, interacts with early‐life stress in predicting psychopathology. Previous results suggest that carriers of the TT genotype of rs1360780 who were exposed to child abuse show differences in structure and functional activation of emotion‐processing brain areas belonging to the salience network. Extending these findings on intermediate phenotypes of psychopathology, we examined if the interaction between rs1360780 and child abuse predicts resting‐state functional connectivity (rsFC) between the amygdala and other areas of the salience network. We analyzed data of young European adults from the general population ( N  = 774; mean age = 18.76 years) who took part in the IMAGEN study. In the absence of main effects of genotype and abuse, a significant interaction effect was observed for rsFC between the right centromedial amygdala and right posterior insula ( p  < .025, FWE‐corrected), which was driven by stronger rsFC in TT allele carriers with a history of abuse. Our results suggest that the TT genotype of rs1360780 may render individuals with a history of abuse more vulnerable to functional changes in communication between brain areas processing emotions and bodily sensations, which could underlie or increase the risk for psychopathology. Abstract : In 774 young European adults, we examined if child abuse and rs1360780 of the FKBP5 gene interact in predicting resting‐state functional connectivity (rsFC) between the amygdala and other areas of the salience network. An interaction was found in rsFC with the right posterior insula, driven by stronger rsFC in TT allele carriers with a history of abuse. After exposure to childhood abuse, individuals with the rs1360780 TT genotype may become more vulnerable to develop psychopathology due to altered amygdala functional connectivity.